DTRA directional transmission and reception algorithms in WLANs with directional antennas for QoS support. - Zhensheng Zhang (IEEE Network : the magazine of global information exchange)
Recent research results show that there are significant gains in throughput to be realized with directional transmission and directional reception compared to using omnidirectional; however, no specific reservation/scheduling algorithms are presented (Su Yi et al., 2003). In this article we propose a novel directional transmit and receive algorithm (DTRA) in wireless local area networks with directional antennas for quality of service support. To the best of our knowledge, all the previous work assumes omnidirectional reception at certain stages of the algorithms. However, the omnireceive requirement makes the protocol vulnerable to jamming. In this article no omniantennas or omnidirectional reception capability is assumed at all. The proposed algorithm exploits the beamforming capabilities of smart antennas to tailor resource access according to the services desired for individual traffic flows while limiting interference, probability of detection, and jamming in the network. Specifically, we present a TDMA-based MAC algorithm for load-dependent negotiation of slot reservations. Our new protocol offers four significant advantages: it assumes directional transmission/reception, it is distributed (i.e., it relies on local information only), it allocates slots to different links dynamically based on demand, and power control is easily carried out during neighbor discovery, reservation, and data transmission with very little overhead. We believe this is the first work on pure directional transmission and reception in wireless ad hoc networks. The algorithm can be used in many commercial and military applications. Preliminary simulation results indicate that DTRA performs much better than IEEE 802.11 for the network considered.